2007
DOI: 10.1038/nmat2045
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a simultaneous red–green–blue reflector using single-pitched cholesteric liquid crystals

Abstract: A cholesteric liquid crystal (CLC) is a self-assembled photonic crystal formed by rodlike molecules, including chiral molecules, that arrange themselves in a helical fashion. The CLC has a single photonic bandgap and an associated one-colour reflection band for circularly polarized light with the same handedness as the CLC helix (selective reflection). These optical characteristics, particularly the circular polarization of the reflected light, are attractive for applications in reflective colour displays with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
123
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(126 citation statements)
references
References 23 publications
2
123
0
1
Order By: Relevance
“…In CLC, the birefringent molecules self-assemble with the director (crystalline) axis arranged in a spiral, with a pitch on the order of the optical wavelength stretching from the UV to the infrared regime, as seen in Figure 12. As a result, CLC's possess not only the advantageous features of liquid crystals such as fabrication ease and low cost, and a very wide spectral dynamic range of operation [68,69], but also the 1-D photonic crystals' unique ability to enhance the nonlinear ultrafast all-optical responses of the CLC constituent molecules [mostly due to the nematic constituent], in addition to the dispersion effect at the photonic band-edges. A typical magnitude of the non-resonant nonlinear index coefficient n 2 is in the order of 10 −14 -10 −13 cm 2 /W, but owing to the photonic crystal band-edge enhancement, the magnitude of the effective n 2 can be as large as 10 −12 -10 −11 cm 2 /W.…”
Section: Ultrafast Pulse Modulations Based On Cholesteric Liquid Crysmentioning
confidence: 99%
“…In CLC, the birefringent molecules self-assemble with the director (crystalline) axis arranged in a spiral, with a pitch on the order of the optical wavelength stretching from the UV to the infrared regime, as seen in Figure 12. As a result, CLC's possess not only the advantageous features of liquid crystals such as fabrication ease and low cost, and a very wide spectral dynamic range of operation [68,69], but also the 1-D photonic crystals' unique ability to enhance the nonlinear ultrafast all-optical responses of the CLC constituent molecules [mostly due to the nematic constituent], in addition to the dispersion effect at the photonic band-edges. A typical magnitude of the non-resonant nonlinear index coefficient n 2 is in the order of 10 −14 -10 −13 cm 2 /W, but owing to the photonic crystal band-edge enhancement, the magnitude of the effective n 2 can be as large as 10 −12 -10 −11 cm 2 /W.…”
Section: Ultrafast Pulse Modulations Based On Cholesteric Liquid Crysmentioning
confidence: 99%
“…Multilayered structures of the dye-doped ChLCs used in the study [114] have revealed lasing thresholds as low as 12 nJ/pulse, which is an order of magnitude lower than that for the equivalent single-layer ChLC cell. Introduction of defects of certain sequences such as Fibonacci [115][116][117], Thue-Morse [118], Rudin-Shapiro [119], etc. is attractive for fabricating the photonic structures with the multiple PhBGs.…”
Section: Defect Modes In Cholesteric Liquid-crystal Lasersmentioning
confidence: 99%
“…[10] Otherwise, superchiral light is required, [11,12] downscaling the helical pitch of the circularly polarized light to the material one. Especially, in the last years, boosted by advanced nanotechnology capabilities, artificial nanomaterials exhibiting chirality have been proposed under several schemes, with the main target to induce large chiro-optical effects related to the polarization control in the linear and non-linear regime.…”
Section: Introductionmentioning
confidence: 99%